Analysis of the Doctor of Public Health (DrPH) training and identity needs in the United States: a qualitative study - Chulwoo Park; Cindy Delgado (BMC, 2023)
Abstract Background The Doctor of Public Health (DrPH) is the highest attainable degree in the field of public health, specifically designed to prepare professionals to address complex public health challenges in practical settings. This study was designed to explore the importance of achieving a shared and uniform understanding of DrPH education, assess the optimal direction for DrPH training, and investigate the specific curriculum requirements by gathering insights from current DrPH students and alumni in the United States. Methods A total of 13 focus group discussions and two in-depth interviews (total participants: 50) were conducted through Zoom to see how DrPH students and alumni assessed their DrPH educational programs. Results Three overarching findings emerged from the analysis of focus group discussions and in-depth interviews. First, participants expressed a preference against a national DrPH board examination, but advocated for a standardized common core curriculum that extends across the entire nation. Second, the ideal direction for DrPH training was perceived to involve a practice-based approach, emphasizing the importance of multi-, inter-, and trans-disciplinary instruction delivered by faculty with practical experience. Last, there was a demand for a DrPH-specific unique curriculum encompassing areas such as mixed method analysis, leadership and management, applied communication, crisis and change management, proficiency in addressing contemporary topics, and tailored applied and integrative learning requirements specific to the DrPH program. Conclusions We explored a range of DrPH training and identity needs among 50 participants, comprised of students and alumni who directly benefit from DrPH education. By considering these inputs, individuals from institutions that offer the DrPH degree can further enhance the quality of public health practice training and make significant contributions to the overall advancement of the field of public health.